PENGARUH PENERAPAN SKS, MOTIVASI EKSTRINSIK, DAN DISIPLIN BELAJAR TERHADAP PRESTASI BELAJAR EKONOMI SISWA KELAS XI IPS SMAN 3 PURWOKERTO - Iryanti, Ikke; Purnomo, Ratno (Soedirman Economics Education Journal; Vol 1 No 1 (2019), 2019)
Abstract The purpose of the study was to analyze the effect of applying credits, extrinsic motivation, and learning discipline on economic learning achievement in class XI IPS SMAN 3 Purwokerto. This research uses a quantitative approach with a survey method. The population of this research was all students of class XI of SMAN 3 Purwokerto. To analyze hypotheses using multiple linear regression analysis. The Conclusions are: 1. The application of the Semester Credit System (SKS) does not influence the economic Significantly learning achievement of students of class XI IPS SMAN 3 Purwokerto; 2. extrinsic motivation has a positive effect on students' achievement of economic learning in class XI IPS SMAN 3 Purwokerto; 3. Learning discipline has a positive economic effect on the learning achievement of students of class XI IPS SMAN 3 Purwokerto; 4. Keywords: SKS application, extrinsic motivation, learning discipline, Learning Achievement.